2020
DOI: 10.1016/j.annonc.2020.03.296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19-infected cancer patients: a retrospective case study in three hospitals within Wuhan, China

Abstract: Background: Cancer patients are regarded as a highly vulnerable group in the current Coronavirus Disease 2019 (COVID-19) pandemic. To date, the clinical characteristics of COVID-19-infected cancer patients remain largely unknown. Patients and methods: In this retrospective cohort study, we included cancer patients with laboratory-confirmed COVID-19 from three designated hospitals in Wuhan, China. Clinical data were collected from medical records from 13 January 2020 to 26 February 2020. Univariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

117
1,706
32
141

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,372 publications
(1,996 citation statements)
references
References 14 publications
(26 reference statements)
117
1,706
32
141
Order By: Relevance
“…They concluded that the infection rate of COVID-19 in cancer patients was higher than the cumulative incidence reported over the same period in Wuhan (0.79% vs 0.37%, OR 2.31 [95% CI, 1.89-3.02]). Zhang et al retrospectively analyzed 28 COVID-19-infected cancer patients (17). Of note, the median age of infected patients was similar in both studies ( 66 and 65 years respectively), and lung cancer was also the most predominant type with more than half of the patients (seven of 12 patients) in the first cohort and 25% (7 of 28) in the second one.…”
Section: Epidemiological Clinical Pathological and Radiographic Feamentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the infection rate of COVID-19 in cancer patients was higher than the cumulative incidence reported over the same period in Wuhan (0.79% vs 0.37%, OR 2.31 [95% CI, 1.89-3.02]). Zhang et al retrospectively analyzed 28 COVID-19-infected cancer patients (17). Of note, the median age of infected patients was similar in both studies ( 66 and 65 years respectively), and lung cancer was also the most predominant type with more than half of the patients (seven of 12 patients) in the first cohort and 25% (7 of 28) in the second one.…”
Section: Epidemiological Clinical Pathological and Radiographic Feamentioning
confidence: 99%
“…Conversely, in the Jing et al cohort, outcome of cancer patients was a secondary endpoint, but authors could conclude that three of 12 patients (25.0%) developed SARS; 1 patient required an ICU admission and 3 deaths (25.0%) were recorded(16). Zhang et al reported a higher rate of adverse events (53.6%) and mortality (28.6%) in their 28 cancer patients cohort, with a higher risk of sever events in patients who had their last anti-tumor treatment within 14 days of the infection (HR=4.079, 95%CI 1.086-15.322, P=0.037) (17).The three above studies(5,16,17) encouraged physicians to withhold or postpone cancer treatment during the epidemic, and this need was mainly urged by Liang et al based on an increased risk of adverse events in patients that received chemotherapy or underwent recent surgery prior to the infection, predisposing them to hematological toxicity and to an immunocompromised state. Regarding patients treated with immunotherapy, no clear data are yet available.…”
mentioning
confidence: 99%
“…2 Data also highlights that hospital admission and recurrent hospital visits are risk factors for SARS-CoV-2 infection, and that receipt of anti-cancer therapy within 14 days of presentation is associated with higher rates of intensive care admission, mechanical ventilation, or death. [3][4][5] Coupled with the significant constraints at upstream healthcare systems levels, it is incumbent upon oncologists to adopt prioritization strategies in order to deliver safe, effective, and feasible care in the setting of a pandemic. We sought to develop recommendations to assist in prioritizing systemic therapies for patients with genitourinary cancers in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Early data from the epidemic in China suggest that a cancer diagnosis is a risk factor for severe events from COVID-19, especially if the patient recently underwent chemotherapy or surgery. [1][2][3][4] Patients with cancer and iatrogenic immunosuppression for the treatment of other medical conditions are likely at even greater risk of complications and death from viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Immunocompromised patients with COVID-19 are also thought to be more likely to have severe adverse events, although the data are still limited. 1,18 Combining the two factors of a cancer diagnosis and an immunosuppressed state intensifies the gravity and complexity of the situation. We report two presentations of head and neck cancer in immunocompromised patients in the setting of this global pandemic and discuss our clinical rationale for the different approaches taken in each case.…”
Section: Introductionmentioning
confidence: 99%